2015
DOI: 10.1017/cem.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Canadian pediatric emergency physician knowledge of concussion diagnosis and initial management

Abstract: Introduction: The diagnosis of concussion is a critical step in the appropriate management of patients following minor head trauma. The authors hypothesized that wide practice variation exists among pediatric emergency medicine physicians in the application of physical and cognitive rest recommendations following an acute concussion. Methods: The authors developed a 35-item questionnaire incorporating case vignettes to examine pediatric emergency physician knowledge of concussion diagnosis, understanding of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…National and international guidelines recommend that youth with a suspected concussion undergo urgent medical assessment and obtain medical clearance prior to returning to full sport activities (46, 50) However, a retrospective population-based study in Ontario from 2003 to 2013 found that only one third of youth sought medical follow-up or clearance following an initial visit for concussion (56). Although the responsibility to provide medical assessment and clearance for youth with concussion generally falls upon primary care providers, surveys conducted among Canadian family medicine physicians, pediatricians and emergency department physicians demonstrate considerable knowledge gaps with a significant proportion failing to provide proper post-injury guidance and care (5760).…”
Section: Current State Of Concussion Care In Canadamentioning
confidence: 99%
“…National and international guidelines recommend that youth with a suspected concussion undergo urgent medical assessment and obtain medical clearance prior to returning to full sport activities (46, 50) However, a retrospective population-based study in Ontario from 2003 to 2013 found that only one third of youth sought medical follow-up or clearance following an initial visit for concussion (56). Although the responsibility to provide medical assessment and clearance for youth with concussion generally falls upon primary care providers, surveys conducted among Canadian family medicine physicians, pediatricians and emergency department physicians demonstrate considerable knowledge gaps with a significant proportion failing to provide proper post-injury guidance and care (5760).…”
Section: Current State Of Concussion Care In Canadamentioning
confidence: 99%
“…Despite the existence of the five different training resources identified in this review, their weak implementation and unknown fidelity and/or effectiveness limits their potential application . Practice variation and evidence‐to‐practice gaps among EPs management of mTBI has been documented, and suboptimal implementation strategies have previously been held responsible for this variation . In this review, the measurement of both knowledge‐based and patient‐centered outcomes was suboptimal; thus, the most effective methods for EP knowledge uptake and practice change remain to be identified.…”
Section: Discussionmentioning
confidence: 97%
“…117,118 The pediatric version of the ONF guidelines published in 2014 also included a targeted, subject-specific evaluation for patients with symptoms lasting more than 1 month. 119 …”
Section: Summary Of the Current Approach To Treating Concussionsmentioning
confidence: 99%